Reliability and Validation of the Children’s Eating Attitudes Test among 10- to 14-Year-Old School Children in Turkey. - Aritici Colak, Gözde; Örkü, Ecem; Ayhan Parmaksız; Murat Bas (Nutrición Clínica y Dietética Hospitalaria, 2022)
Introduction: Eating disorders (ED) onset occurs commonly during adolescence and this is a very critical period of life in the context of developmental perspectives because adequate nutrition is necessary for optimal growth and development. Nutritional disorders can be harmful and cause extreme and potentially permanent physical and psychological consequences. Therefore, defining the eating disorder in its early stages is important. Objective: The goal of this study was to translate the Children’s Eating Attitude Test (CHEAT) into Turkish and establish its validity and reliability among Turkish schoolchildren. Methods: The study was conducted on students from two private and two public primary schools. After delivering invitations to suitable classes, informed consents that had been written by participants and parents were collected. Results: The research comprised 352 children between the ages of 10 and 14, including 222 females and 130 boys. Minimum factor loading is 0.597 and total percentage of explained variance is 58.04 The CFA supported these findings, since the 15-item scale had a greater goodness-of-fit and exploratory component analysis generated four factors. Conclusion: Analysis of data showed that the ChEAT scale is a valid and reliable measurement tool available in Turkey. It is thought that the ChEAT scale will contribute to studies on eating disorders in children aged between 10-14 years.